Greenhouse and field assessment of biological and chemical agents against guava decline - Da Silva Alves, Cintia [UNESP]; Costa Starling, Renan Zappavigna [UNESP]; Rodrigues, Lilian Lagen; Nascimento, Maria Laura Urbano; De Vargas, Amanda Dutra; Dos Reis, Ualace Oliveira; De Resende Camara, Guilherme; Moraes, Wilian Bucker; Da Silva Xavier, André; Alves, Fábio Ramos (FapUNIFESP (SciELO), 2021)
Guava decline is a complex disease resulting from the parasitism by Meloidogyne enterolobii (Me), which predisposes the plant to root rot caused by Fusarium sp. Three in vitro experiments were carried out with the aim of: (i) selecting the Fluensulfone dosage capable of causing Me mortality; (ii) verifying the effect of Fluensulfone on Pochonia chlamydosporia and Trichoderma harzianum; (iii) evaluating the effect of Pochonia chlamydosporia and Trichoderma harzianum in pure doses and in association with Fluensulfone on Me mortality. Fluensulfone at 2 L.ha-1 had no effect on fungi. The associated and pure doses of treatments had a significant effect on Me mortality. A field experiment was also carried out in a guava orchard where decline occurred. The following treatments were tested: Fluensulfone; P. chlamydosporia; P. chlamydosporia + Fluensulfone; T. harzianum; T. harzianum + Fluensulfone; Carbofuran, and control. All treatments reduced Me population, since relative efficiency was higher than 80%. Fluensulfone used alone or in combination with biological nematicides provided an increase in guava productivity. Maintaining Me population low in the field is an important option for increasing productivity and reducing the losses suffered by farmers.significant effect on Me mortality. A field experiment was also carried out in a guava orchard where decline occurred. The following treatments were tested: Fluensulfone; P. chlamydosporia; P. chlamydosporia + Fluensulfone; T. harzianum; T. harzianum + Fluensulfone; Carbofuran, and control. All treatments reduced Me population, since relative efficiency was higher than 80%. Fluensulfone used alone or in combination with biological nematicides provided an increase in guava productivity. Maintaining Me population low in the field is an important option for increasing productivity and reducing the losses suffered by farmers.
Avaliação no campo e em casa de vegetação de agentes biológicos e químicos contra o declínio da goiaba
Keywords: Fluensulfone; Meloidogyne enterolobii; Pochonia chlamydosporia; Trichoderma harzianum